Tropical cyclogenesis via convectively forced vortex Rossby waves in a three-dimensional quasigeostrophic model - Enagonio, Janice, author; Montgomery, Michael T., author (Colorado State University. Libraries, 1998)
This work investigates the problem of tropical cyclogenesis in three dimensions. In particular, we examine the interaction of small-scale convective disturbances with a larger scale vortex circulation in a nonlinear quasigeostrophic balance model. Convective forcing is parameterized by its estimated net effect on the potential vorticity field. Idealized numerical experiments show that vortex intensification proceeds by ingestion of like-sign potential vorticity anomalies into the parent vortex and expulsion of opposite-sign potential vorticity anomalies during the axisymmetrization process. For the finite amplitude forcing considered here the weakly nonlinear vortex Rossby wave, mean-flow predictions for the magnitude and location of the spinup are in good agreement with the model results. Vortex development is analyzed using Lagrangian trajectories, Eliassen-Palm flux vectors, and the Lorenz energy cycle. Using numerical estimates of the magnitude of PV injection based on previous observational and theoretical work, we obtain spinup to a 15 ms-1 cyclone on realistic time scales. Simulation of a midlevel vortex with peripheral convection shows that axisymmetrization results in the spinup of a surface cyclone. The axisymmetrization mechanism demonstrates the development of a warm-core vortex. The relative contribution from eddy heat fluxes and eddy momentum fluxes to the warm core structure of the cyclone is investigated. The vortex spinup obtained shows greater than linear dependence on the forcing amplitude, indicating the existence of a nonlinear feedback mechanism associated with the vortex Rossby waves. Building on recent work by several authors, this work further clarifies the significance of the axisymmetrization process for the problem of tropical cyclogenesis. The theory is shown to be consistent with published observations of tropical cyclogenesis. Further observational tests of the theory, specific to the dynamics examined here, are proposed.
July 1998.
Also issued as Janice Enagonio's thesis (M.S.) -- Colorado State University, 1997.
Keywords: Cyclones -- Tropics; Convection (Meteorology); Vortex-motion